Gender Equity Perceptions Related to College and University Campus Recreation Programs. Issue 1 (April 2014) - Schneider, Robert C.; Stier, William F.; Kampf, Steve
The extent to which gender equity–related items were perceived to be provided for equally in women's club and intramural sports programs when compared with men's programs was sought. Subjects consisted of 1000 National Intramural Recreational Sports Association (NIRSA) members/professionals; 58.8% were male and 41.2% female. A five-point Likert-scale questionnaire ranging from strongly agree to strongly disagree was used to acquire data. Of the 21 total items on the questionnaire, 10 were relevant to club and intramural sports programs, 10 to club sports programs and one to intramural sports programs. Chi square values were computed to determine if statistically significant differences existed between males and females for club sports and also for intramural sports. Findings revealed that each of the 10 shared gender equity–related items for women's intramural sports programs were being provided for equally at higher perceived rates of agreement when compared with women's club sports programs (the overall difference being 11.7%). The differences (unfavorable for women's club sports programs) were highest for off-campus publicity (14.9%) and on-campus publicity (14.8%). For all items, less than 70% of the professionals perceived women's club sports programs as being provided for equally when compared with men's and approximately three-fourths believed the same for women's intramural programs.